Arthropods associated with soybean crops (Revista de Ciências Agroveterinárias, 2011)
The objective this research was to study the arthropods associated with soybean Glycine max (L.) Merrill crops in Chapecó, Santa Catarina State, Brazil. The samples were collected from 2005/06 and 2006/07 and 2007/08 seasons applied weekly the ground-cloth method in eight points distributed among the crops between V4 and R8 plants stages. The samples were sorting in laboratory and the data were organized by date and taxon. Phytophagous insects totaled 5,278 individuals and natural enemies were 2,203. The stink bugs Nezara viridula (L.) and Piezodorus guildinii (West.) (both Hemiptera: Pentatomidae) are as "key" pests of soybean crops occurring mainly on the reproductive plants phase. Anticarsia gemmatalis Hüebner (Lepidoptera: Noctuidae) and Diabrotica speciosa Germar (Coleoptera: Chrysomelidae) are "secondary" pests more "frequent" infesting the plants during the vegetative and early reproductive stages. Lebia concinna Brullé (Coleoptera: Carabidae) and bugs Geocoris spp. (Hemiptera: Lygaeidae) and predatory ants and spiders are predators "constant" and more "frequent" in crops.
Keywords: Glycine max; Pests; Natural enemies.